Impact of Intense Physical Exercise on Athletes’ Hearts – Adaptation, Risk, and Prevention - Bollin, Pawel; Szymczak, Urszula; Lachór, Wojciech Wiesław; Solarz, Monika Barbara; Piekarska, Julia; Solarz, Justyna Maria; Wawrzyńców, Jakub Tomasz; Cyrkler, Weronika; Robak, Jakub; Telega, Stanisław (Quality in Sport, 2025)
Intensive physical activity, especially when performed regularly and at high levels, leads to characteristic cardiovascular adaptations called "athlete’s heart" (AH). These physiological changes include left ventricular hypertrophy, atrial enlargement, and electrophysiological modifications, reflecting the heart’s adaptive response to increased demands during exercise. While typically benign, these adaptations can closely mimic pathological conditions like hypertrophic cardiomyopathy (HCM), complicating diagnosis and requiring careful differentiation to avoid unnecessary restrictions on athletic participation. Ethnic variability in cardiac remodeling, particularly among athletes of African descent, increases the potential for misdiagnosis and unjustified disqualification from sports. Although generally considered physiological, athlete’s heart may exhibit proarrhythmic properties, elevating the risk of cardiac arrhythmias in some individuals. Prolonged, high-intensity exercise, especially in middle-aged male athletes, is linked to a greater incidence of atrial fibrillation, transient right ventricular dysfunction, and other rhythm disturbances. Diagnostic tools such as electrocardiography (ECG) and transthoracic echocardiography remain essential in differentiating physiological from pathological findings, though newer imaging techniques and biomarkers are being evaluated for better accuracy. Additionally, the use of doping substances and energy drinks poses an added burden on the cardiovascular system, warranting further research and clinical attention. This review aims to analyze current knowledge on both physiological and pathological cardiac adaptations to exercise, focusing on assessing and preventing cardiovascular risks in athletes.